Determinants of capital structure: empirical evidence from Vietnamese listed construction companies - Nguyen, Thuy Anh; Le, Thi Thanh Huyen (Journal of International Economics and Management, 2015)
This paper employs a new database containing the market and accounting data (from 2007 to 2013) of more than 100 Vietnamese listed construction companies to describe their capital structure characteristics. As a result, we found that business risk, tangibility and growth also considerably impact on debt-to-capital ratio while size and tax are insignificantly associated with the capital structure of Vietnamese construction firms. In addition, different from other researches in other countries, Vietnamese construction companies tend to have much lower long-term debt.